Kortárs Médeia kamaszoknak: (Marie Goudot: Médée, la Colchidienne) - Pataki, Elvira (Studia Litteraria, 2017)
Médée, la Colchidienne (Medea the Colchian woman) is a novel written for adolescents by the French Hellenist and writer Marie Goudot, published in 2002. Rooted in the still very rich French literary tradition about the princess, the novel of Goudot seems to adhere to a particular way of interpretation of the myth. This one considers the well-known portrait of Medea, an infanticide witch, as a Euripidean forgery conceived to destroy the originally highly positive image of the wise-woman and benevolent healer. One of the most important representatives of this rehabilitating lecture is Medea. Stimmen, a German novel published in 1996 by Christa Wolf, strongly influenced by psychoanalysis and feminism. The aim of the present article is twofold. Firstly, we would like to investigate the Wolfian inspiration of the French novel. Secondly, we examine the special role attributed to children in the narrative, and the complexity of mother-child relation in the novel by which Goudot is able to add a new aspect to our traditional way of thinking about Medea.